Performance Evaluation Of Feed And Recycle Gas Chiller Influence On Environmental Conditions In The Production Process Plant - Astuty Astuty (Universitas Sriwijaya, 2016)
Heat transfer by convection is strongly influenced by the geometric shapes of heat exchangers and three dimensionless number, the Reynolds number, Nusselt number and Prandtl number with the environmental conditions of the surrounding air. Any environmental influences cause actual results and theoretical conditions differ. This is one of the problems at the plant in the production process results, especially the heat exchanger type of chiller. In this paper aims to determine the impact of the ammonia production process of the influence of changing environmental conditions and to apply the concept of heat and mass transfer in the Chiller as knowledge development models ammonia optimum production equipment in the ammonia. In this study, measurements were performed during the morning, afternoon, evening, and night on normal weather and rain by using thermo-anemometer and thermo-hygrometer. The results showed an increase in heat during heavy rains and decrease the heat when the normal environmental conditions. With the highest increase in the heat on the morning of 14 July 2015 where the air temperature was recorded at 26.3 â„ƒ, the speed of 6.79 m / s, the air flow rate of 19 688 Watt heat and mass flow rate of the ammonia evaporates increased 49.797 kg / h to with 50.368 kg / h. Mass flow rate that evaporates due to the heat transfer air is not decreased by more than 1% despite the chiller effectiveness decreased from 90.422% to 61.259% due to boundary conditions which allowed fouling factor.